Architecture of Mobile Web Application for Generating Dynamic Route Map - Abdullah, Muhammad Haziq Lim; Abdul-Aziz, Azlianor; Sulong, Muhammad Suhaizan; Kamalrudin, Massila (North Atlantic University Union (NAUN), 2008)
Integrated Light Rail Transit (LRT) System in the capital of Malaysia connects some key districts where historical places, interesting places, business areas and shopping malls are concentrated. The train services are running independently but have points where they have interchanges. This may leads the traveler facing difficulty when they are choosing incorrect destination station especially on different LRT lines which contribute to time consuming and high costing. Thus, we present an architecture in developing mobile application that runs on a Personal Digital Assistant (PDA) to provide the solution for traveler to reach the desired destination. It is use to dynamically generate dynamic route map by determining the nearest station according to the specific places. The architecture, web components and its implementation are proposed and discussed in this paper.